Ewing's Sarcoma/Primitive Neuroectodermal Tumor Arising from the Adrenal Gland: A Case Report and Literature Review. Issue 3 (May 2013) - Sasaki, Takeshi; Onishi, Takehisa; Yabana, Tadashi; Hoshina, Akira
We report a rare case of Ewing's sarcoma (ES)/primitive neuroectodermal tumor (PNET) arising from the adrenal gland. A 17-year-old Japanese woman presented with left upper abdominal pain and high fever. Computed tomography and magnetic resonance imaging revealed a 15×10 cm tumor replacing the adrenal gland. Preoperative diagnosis was an adrenocortical carcinoma. Resection of the tumor was performed. We obtained the final diagnosis of ES/PNET by immunohistochemical molecular study with positive staining for the MIC2 gene product (CD99) and a Ewing sarcoma breakpoint region 1 (EWSR1) gene rearrangement. Local recurrence was observed one month after the surgery. The patient was then treated with systemic chemotherapy and localized radiotherapy.